Erratum: Nanoscale visualization of functional adhesion/excitability nodes at the intercalated disc - Alejandra Leo-Macias (Nature Portfolio, 2016)
Nature Communications 6: Article number: 10342 (2015); Published: 20 January 2016; Updated: 22 February 2016 The author Eli Rothenberg was incorrectly omitted from the list of corresponding authors in this Article and authors Julia Gorelik and David Fenyö were incorrectly listed as corresponding authors.